Pemanfaatan Material Daur Ulang dalam Pembuatan Tempat Sampah dan Perancangan Banner Lingkungan yang Efektif untuk Mendorong Kesadaran Lingkungan di SMK N 1 Merek - Girsang, Hamidah Nurul Badri; Harahap, Jehanda Alhafiz (Maslahah: Jurnal Pengabdian Masyarakat, 2024)
The increase in environmental awareness among the younger generation has become crucial considering the growing issues of waste and environmental pollution. This community service program aims to enhance environmental awareness at SMK N 1 Merek by utilizing recycled materials in the creation of trash bins and the design of effective environmental banners. The program involves students, teachers, and school officials in various stages, starting from the collection of recyclable materials, the construction of trash bins, to the design and installation of environmental banners in the school area. The results of the activities indicate that student participation in this program has successfully improved their understanding and awareness of the importance of waste management and maintaining a clean environment. In conclusion, this community service program has successfully fostered positive changes in students' behavior towards the environment and encouraged the formation of an environmentally conscious culture within the school.